2012
DOI: 10.2478/cttr-2013-0913
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fertilization for Optimizing the Quality and Yield of Shade Grown Cuban Cigar Tobacco: Required Nitrogen Amounts, Application Schedules, Adequate Leaf Nitrogen Levels, and Early Season Diagnostic Tests

Abstract: Nitrogen (N) fertilizers have a decisive influence on the yield and quality of tobacco. Yield, percentage of plant N, wrapper leaf quality, and nicotine content are all important quality characteristics in tobacco growing. This work is an attempt to provide a tool for optimizing mineral N nutrition for Cuban cigar tobacco, using a strategy that links N supply with leaf N concentration and wrapper yield. Similar approaches developed worldwide have mainly involved Virginia and Burley tobacco types but not Cuban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
2
6
1
Order By: Relevance
“…For the Fh product, there was a significant location × N fertilization interaction (Table 3) since Fh yield increased with fertilization in 9 out of 11 locations and the increments were significant up to 200 kg N ha !1 in B1, B2, B6, B9 and B10, but only up to NFP treatment in B4, B5, B8 and B11 locations ( Figure 2). These results were similar to those previously reported for Burley (6) and Cuban tobacco (10). Moreover, Fh yield did not change significantly with N treatments at B3 while it decreased with N200 treatment at B7 location ( Figure 2).…”
Section: Plant Growth Yield and Quality Soil N Contentsupporting
confidence: 91%
See 2 more Smart Citations
“…For the Fh product, there was a significant location × N fertilization interaction (Table 3) since Fh yield increased with fertilization in 9 out of 11 locations and the increments were significant up to 200 kg N ha !1 in B1, B2, B6, B9 and B10, but only up to NFP treatment in B4, B5, B8 and B11 locations ( Figure 2). These results were similar to those previously reported for Burley (6) and Cuban tobacco (10). Moreover, Fh yield did not change significantly with N treatments at B3 while it decreased with N200 treatment at B7 location ( Figure 2).…”
Section: Plant Growth Yield and Quality Soil N Contentsupporting
confidence: 91%
“…Surprisingly, fertilization increased yield of wrappers up to the NFP treatment, which for that location was just 113.5 kg N ha !1 , without any significant increase at the N200 treatment (Table 3). These results are different from those for Cuban tobacco as reported by BORGES et al (10) who found that a supply of N around 190 kg ha !1 resulted in maximum high quality wrapper yield from the middle stalk position. In addition, in that study the wrapper production accounted for 75% of total production of this commercial type, much greater than that obtained at 200 kg N ha !1 in the present experiment which was only 14%, due to foliar diseases, mainly caused by infestations of tobacco flea beetle (Epitrix hirtipennis (Melsheimer)) very widespread in that area, or mechanical injuries.…”
Section: Plant Growth Yield and Quality Soil N Contentcontrasting
confidence: 87%
See 1 more Smart Citation
“…Our results show that the percentage of nitrate-N, calculated on the total N accumulated by plants at the end of the growing period, increased with increasing N fertilization up to 120-240 kg N ha -1 under stressed conditions and up to 360 kg N ha -1 under irrigated ones (data not shown). Consistent with our results, Borges et al (2012) also reported optimal fertilization levels around 140-190 kg N ha -1 for Cuban cigar tobacco, which further highlights the site-specific requirements for optimal N fertilization. In our conditions, DM accumulation, LA expansion and weight of cured leaves did not improve at N rates above 240 kg ha -1 .…”
Section: Resultssupporting
confidence: 90%
“…Wrapper tobacco is the outer part of the cigar which is thin in texture and usually dominates the flavor of a cigar. The expensive hard-to-obtain wrapper leaves are acquired from plants grown in shady environments which are used as a cover towards the end of manufacturing highquality cigars [19]. Shading or low light (LL) conditions are a key and necessary cultivation technique in cigar wrapper tobacco production.…”
Section: Introductionmentioning
confidence: 99%